IMPROVING NATURALIST INTELLIGENCE OF 5-6 YEAR OLD CHILDREN THROUGH PROJECT BASED LEARNING - Taufik, Eneng Sri Susilawati, Suci Aprilyati Ruiyat (Jurnal Pendidikan dan Penelitian Serumpun Mendidik, 2024)
Early childhood is in a crucial stage of development and has the right to grow and develop optimally, especially during the golden period of intelligence. Naturalist intelligence, defined as the ability to recognize and categorize elements in nature, is very important to develop. This study aims to improve the naturalist intelligence of children aged 5-6 years at PAUD Raflesia through a learning model, Project Based Learning (PBL). Initial observations showed that children had low naturalist skills. The conventional method applied at the PAUD proved to be less effective, so a change in approach that is more fun and interactive is needed. In this study, a Classroom Action Research (CAR) design was applied with three stages: planning, action, and reflection. The results showed a significant increase in children's naturalistic intelligence, from 34.44% in the pre-research to 49.47% in cycle I and reached 90.20% in cycle II. This increase reflects the effectiveness of PBL in motivating children to actively learn and care for the environment. This study suggests the use of learning models that match children's interests as well as varied and fun activities to support further development of naturalist intelligence.